Association of Maternal Buprenorphine or Methadone Dose with Fetal Growth Indices and Neonatal Abstinence Syndrome - Coulson, Carol C.; Lorencz, Erin; Rittenhouse, Katelyn; Ramage, Melinda; Lorenz, Kathleen; Galvin, Shelley L. (American Journal of Perinatology, 2019)
Objective Our objective was to compare fetal growth and incidence of neonatal abstinence syndrome requiring treatment across pregnant women with opioid use disorders on two types and two dose categories of medication-assisted treatment.Study Design A retrospective cohort study was conducted in a comprehensive, perinatal program in western North Carolina comparing growth percentiles on third-trimester ultrasound and at birth, and diagnosis of neonatal abstinence syndrome requiring treatment. Singletons were exposed in utero to low- to moderate-dose buprenorphine (≤16 mg/day; n = 70), high-dose buprenorphine (≥17 mg/day; n = 36), low- to moderate-dose methadone (≤89 mg/day; n = 41), or high-dose methadone (≥90 mg/day; n = 74). Multivariate analysis of variance with posthoc Bonferroni comparisons (p ≤ 0.01) and multinomial logistic regressions (adjusted odds ratio, 99% confidence interval) were conducted.Results Differences in neonatal outcomes reached statistical significance for larger head circumference for buprenorphine doses (p = 0.01) and for longer length (p < 0.01) and lower odds of neonatal abstinence syndrome requiring treatment (p < 0.01) with low- to moderate-dose buprenorphine versus high-dose methadone.Conclusion Among pregnant women using medication-assisted treatment for opioid use disorders, low- to moderate-dose buprenorphine (≤16 mg/day) was associated with the most favorable neonatal outcomes. However, more rigorous control of confounders with a larger sample is necessary to determine if low- to moderate-dose buprenorphine is the better treatment choice.
Keywords: neonatal abstinence syndrome; opioid use disorder in pregnancy; medication-assisted treatment